(untitled) (مجلة الواحات للبحوث والدراسات, 2021)
In This Paper We Present A Brief Biography Of One Of The Scholars Of The Eleventh Century AH, Sheikh Abu Abdullah Mohammed Touati, This Person, Who Served The Arabic Language Both In Terms Of Teaching And Publishing. We Will Attempt To Present Him And His Writings, And Tackle Some Of His Methodology In Morphologic Writings In His Book, Charh Lamiyat Alafaal Libn Malek, Which Included Many Benefits, And Contained Many Topics Of Value. The Sheikh Was Not Just A Transmitter, But He Was A Prominent Figure Who Expressed His Opinions Regarding Many Morphological Questions. It Is Worth Mentioning That This Study Is The First Work Dealing With The Efforts Of Sheikh Mohammed Touati, Despite His Contributions In The Field Of Grammatical And Epigraphic Writings, His Writings Remain Neglected And Was Not So Much Studied. We Hope That This Study Will Play A Role In Presenting Him And His Writings. Keywords- Methodology Of Writing, Morphology, Mohamed Touati.